Performance improvement of solar hot water system by reducing solar irradiation from solar collector and solar tank - Khan, Bonny Amin; Islam, Md. Sanzidul Islam; Ferdous, Jannatul; Rahi, Nabil Shaker (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2011.